Efficient Perovskite Photovoltaic‐Thermoelectric Hybrid Device. Issue 13 (22nd January 2018) - Xu, Ling; Xiong, Yan; Mei, Anyi; Hu, Yue; Rong, Yaoguang; Zhou, Yinhua; Hu, Bin; Han, Hongwei
Abstract: An efficient perovskite photovoltaic‐thermoelectric hybrid device is demonstrated by integrating the hole‐conductor‐free perovskite solar cell based on TiO2 /ZrO2 /carbon structure and the thermoelectric generator. The whole solar spectrum of AM 1.5 G is fully utilized with the ≈1.55 eV band gap perovskite (5‐AVA) x (MA)1− x PbI3 absorbing the visible light and the carbon back contact absorbing the infrared light. The added thermoelectric generator improves the device performance by converting the thermal energy into electricity via the Seebeck effect. An optimized hybrid device is obtained with a maximum point power output of 20.3% and open‐circuit voltage of 1.29 V under the irradiation of 100 mW cm −2 . Abstract : By utilizing the whole AM 1.5 G solar spectrum energy, an efficient perovskite photovoltaic‐thermoelectric hybrid device is demonstrated by integrating the perovskite solar cell based on carbon electrode and the thermoelectric generator. An optimized hybrid device is obtained with a maximum point power output of 20.3% and open‐circuit voltage of 1.29 V under the irradiation of 100 mW cm −2 .